(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Background: Cerebral palsy (CP) is the most common chronic childhood disability of today. Health care needs are present in these children who require health services to manage their functional disability. It can change according to the age group and severity of the condition. In the current healthcare system, little is known about priorities and needs for the children with cerebral palsy especially in reference to Indian contextual situations and how these needs may differ based on the child’s age and motor function. Methods: A cross sectional survey design is used in the study. 83 parents of children with cerebral palsy and their treating physiotherapists were selected in the study based on the inclusion and exclusion criteria. Participants were divided into 3 groups based on the age of the children. Self designed questionnaire was given to the parents and the physiotherapists to select the health care needs for the children. One time data collection was done over the period of 3 months. Conclusion: The study also shows that mostly parent’s needs are considered by physiotherapists for their goal settings. Most of the time parents’ needs and the physiotherapist’s goals are found to be similar.